Transforming conversations : feminism and education in Canada since 1970 - Wallin, Dawn, 1971-; Wallace, Janice, 1944- (McGill-Queen's University Press, 2018)
"This edited collection considers, "What effect, if any, has feminism had on Canadian education since the 1970 Royal Commission on the Status of Women (RCSW), and to what end?" Dawn Wallin and Janice Wallace have edited a collection of chapters that consider these questions within changing social conditions in educational contexts in Canada. Part I of the book, for example, draws on liberal feminism to explore the historical context in which feminists/female educators spoke up for women's rights in formal education systems in Canada from the 1960s to the 1990s. In doing so, these women reshaped education systems in K-12 and university faculties of education. Part II explores the necessity for feminist re/theorizing of educational leadership as women moved into formal leadership roles across education sectors. Part III troubles feminist theory and activism in an education system that is ostensibly more "inclusive" yet remains bounded within Western, colonial, neoliberal ideologies. The Coda revisits themes and extends the discussion by exploring the possibilities for feminism and pedagogy within and through aesthestics and the arts. The editors conclude the book by considering the complex effects feminism has had, and continues to have, on Canadian education, by acknowledging voices that are absent from the text, and inviting readers to continue transformative feminist conversations."--